2003
DOI: 10.1073/pnas.2134173100
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the hidden atom in graphite by low-temperature atomic force microscopy

Abstract: Carbon, the backbone material of life on Earth, comes in three modifications: diamond, graphite, and fullerenes. Diamond develops tetrahedral sp 3 bonds, forming a cubic crystal structure, whereas graphite and fullerenes are characterized by planar sp 2 bonds. Polycrystalline graphite is the basis for many products of everyday life: pencils, lubricants, batteries, arc lamps, and brushes for electric motors. In crystalline form, highly oriented pyrolytic graphite is used as a diffracting element in monochromato… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
127
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(143 citation statements)
references
References 31 publications
14
127
0
2
Order By: Relevance
“…4 were ≈ 0.3 nm/s, therefore time delays in the acquisition channels are negligible and the I, γ and ∆E ts images match precisely in forward and backward scans. In our previous simultaneous STM/AFM measurement on graphite [17], we found a lateral shift of 68 pm of the current maxima with respect to the corresponding γ maxima. While the tip is not perfectly symmetric with respect to the z-axis (see caption Fig.…”
mentioning
confidence: 60%
See 2 more Smart Citations
“…4 were ≈ 0.3 nm/s, therefore time delays in the acquisition channels are negligible and the I, γ and ∆E ts images match precisely in forward and backward scans. In our previous simultaneous STM/AFM measurement on graphite [17], we found a lateral shift of 68 pm of the current maxima with respect to the corresponding γ maxima. While the tip is not perfectly symmetric with respect to the z-axis (see caption Fig.…”
mentioning
confidence: 60%
“…While the tip is not perfectly symmetric with respect to the z-axis (see caption Fig. 4), it is evidently more symmetric than in [17]. Arai and Tomitori [25] have recently shown that force interactions are also a function of bias.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…1) stands out, as it is the configuration of layers in natural graphite. 24,28 Alternative configurations like AA stacking were found in ab initio calculations to be energetically unfavorable; 29 they can, however, be thought of as either mechanically shifted samples or sections of curved bilayers (e.g., sections of two shells in a large multiwall carbon nanotube) where the alignment unavoidably varies over distance. Compared to the Hofstadter butterfly of a single sheet of graphene, 22 two asymmetries are visible in all three plots: The electron-hole symmetry (E ↔ −E) is broken down by the interlayer coupling already at zero magnetic field: while the lowest-energy states of a single graphene layer have constant phase over all atoms and can couple efficiently into symmetric and antisymmetric hybrid states of the bilayer system, the states at high energies have alternating phases for neighboring atoms, so interlayer hybridization is prohibited by the second-nearest-neighbor interlayer coupling.…”
Section: Norbert Nemec and Gianaurelio Cunibertimentioning
confidence: 99%
“…Dynamic AFM [1] in the frequency modulation (FM) mode [2] has resolved the true geometric structure of a broad range of materials [3][4][5]. FM AFM experiments on carbon-based materials [6][7][8][9][10][11][12][13] show atomic contrast in Δf images and, depending on the setup, in the dissipation channel. While the origin of the dissipation is not well understood, the Δf contrast has been linked with the nature of the tip-sample interaction [14].…”
mentioning
confidence: 99%